Spillover effects among financial institutions: A state-dependent sensitivity value-at-risk approach - Zeno Adams; Roland Füss; Reint E. Gropp (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
In this paper, we develop a state-dependent sensitivity value-at-risk (SDSVaR) approach that enables us to quantify the direction, size, and duration of risk spillovers among financial institutions as a function of the state of financial markets (tranquil, normal, and volatile). Within a system of quantile regressions for four sets of major financial institutions (commercial banks, investment banks, hedge funds, and insurance companies) we show that while small during normal times, equivalent shocks lead to considerable spillover effects in volatile market periods. Commercial banks and, especially, hedge funds appear to play a major role in the transmission of shocks to other financial institutions. Using daily data, we can trace out the spillover effects over time in a set of impulse response functions and find that they reach their peak after 10 to 15 days.
urn:nbn:de:hebis:30:3-305737
Keywords: G01; G10; G24; 330; Risk spillovers; state-dependent sensitivity value-at-risk (SDSVaR); quantile regression; financial institutions; hedge funds